2020
DOI: 10.1097/brs.0000000000003761
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Reconstruction of Sagittal Alignment According to Global Alignment And Proportion Score Can Reduce Adjacent Segment Degeneration After Lumbar Fusion

Abstract: Study Design. A retrospective study Objective. The aim of this study was to investigate the ability of Global Alignment and Proportion (GAP) score to predict the occurrence of adjacent segment degeneration (ASD) after fusion surgery for lumbar degenerative diseases. Summary of Background Data. The recently developed GAP score was applied to predict postoperative complications for adult spinal deformity, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Several studies report conflicting results on the GAP score's ability to predict MCs [15][16][17][18][19][20][21][22][23][24]. To our best knowledge, very few studies have specifically investigated the discriminatory power and threshold of the GAP score for those [15,16,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies report conflicting results on the GAP score's ability to predict MCs [15][16][17][18][19][20][21][22][23][24]. To our best knowledge, very few studies have specifically investigated the discriminatory power and threshold of the GAP score for those [15,16,24].…”
Section: Discussionmentioning
confidence: 99%
“…The strength of this study is the relatively long follow-up time. To our best knowledge, there are very few long-term studies on the evaluation of the GAP score with more than five years of follow-up, as most studies meet a minimum follow-up period of two years [15,16,[18][19][20][21][22][23]. In addition, we had an established clinical care team made up of highly experienced spine surgeons and nurses, and patient reachability for controls in the relatively stable catchment area was high.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, long-segment fusion will further increase the occurrence of ASD compared with either short-segment fusion or other non-fusion approaches ( 20 ). The long-segment fusion might affect the global sagittal alignment of the lumbar spine and increase the ROM of adjacent segments compared with the short-segment fusion ( 21 ). This observation is consistent with the findings in our study; we also found that the occurrence of ASD is significantly increased in the long-segment fusion group compared with that in the short-segment fusion group ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…7 8 9 ASD may compromise the operative results and even might require reoperation. Risk factors for ASD after lumbar fusion include high body mass index (BMI), 10 longer fusions, 11 intraoperative damage to the facet joint of adjacent segment, 12 destruction of posterior stabilizing structures, presence of ASD preoperatively, 2 10 decompressive surgery on adjacent segments, 1 unsatisfied postoperative global alignment and proportion score, 13 among others.…”
Section: Discussionmentioning
confidence: 99%